Development and feasibility testing of a chest rig resistance band for student-athlete strength training - Amrullah, Ramdani; Suhairi, Muhammad; Arifin, Zainal; Asmutiar; Aji, Tri (Journal Sport Area, 2025)
Background: Strength training is essential for developing physical performance in student-athletes, yet existing resistance-band tools generally target isolated limb movements and lack a wearable, integrated design. This creates a gap in the availability of portable and ergonomic training equipment suitable for the physical characteristics of adolescent athletes. Objective: This study aimed to develop a chest rig resistance band as a wearable strength-training device and to evaluate its feasibility and effectiveness. Methods: This research employed a mixed-method Research and Development (R&D) approach involving expert validation (three experts), a small-scale trial (12 student-athletes), a large-scale trial (60 student-athletes), product revisions, and an effectiveness test with 14 athletes. Data were analyzed using qualitative descriptive techniques for expert feedback and quantitative descriptive analysis for validation scores and performance improvements. Finding/Results: The Body Chest Rig Resistance Band RSZT 01 demonstrated high feasibility based on expert evaluations (81.94%-90%, very feasible category). Small-scale and large-scale trials also showed very feasible results (93% and 92%). Effectiveness testing revealed performance improvements, indicating that the device supports functional strength training for adolescent athletes. Conclusion: The Body Chest Rig Resistance Band RSZT 01 is feasible and effective as a portable, wearable strength-training device for student-athletes, offering a practical alternative to conventional equipment. Future studies should test the device on larger populations and over longer training periods to further validate its effectiveness.